1998
DOI: 10.1111/j.1469-7793.1998.325bt.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of receptor kinase in short‐term desensitization of cardiac muscarinic K+ channels expressed in Chinese hamster ovary cells

Abstract: The cardiac muscarinic receptor‐K+ channel system was reconstructed in Chinese hamster ovary (CHO) cells by transfecting the cells with the various components of the system. The activity of the muscarinic K+ channel was measured with the cell‐attached configuration of the patch clamp technique. In CHO cells transfected with the channel (Kir3.1/Kir3.4), receptor (hm2) and receptor kinase (GRK2), on exposure to agonist, there was a decline in channel activity as a result of desensitization, similar to that in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…CaR⌬886-EGFP may desensitize normally because the amino acid residues between 868 and 886 retard access of the proteins involved in desensitization to the relevant phosphorylation site(s). Direct interactions between G protein-coupled receptor kinases and possibly arrestin with muscarinic receptors have been functionally demonstrated (44), although the consensus binding site(s) on the receptor have not been identified. Deletion of the amino acid residues of CaR between 868 and 886 may expose potential regulatory protein interaction site(s), leading to more rapid and complete phosphorylation and desensitization of CaR.…”
Section: Discussionmentioning
confidence: 99%
“…CaR⌬886-EGFP may desensitize normally because the amino acid residues between 868 and 886 retard access of the proteins involved in desensitization to the relevant phosphorylation site(s). Direct interactions between G protein-coupled receptor kinases and possibly arrestin with muscarinic receptors have been functionally demonstrated (44), although the consensus binding site(s) on the receptor have not been identified. Deletion of the amino acid residues of CaR between 868 and 886 may expose potential regulatory protein interaction site(s), leading to more rapid and complete phosphorylation and desensitization of CaR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work to define the mechanisms of GIRK desensitization suggested desensitization was resolved into fast and slow phases, where the fast phase is explained by I KACh channel dephosphorylation 33 and RGS protein GAP activity 34 and the slow phase involves G protein receptor kinase activity. 35,36 Because RGS4 has not been implicated in the regulation of kinases or phosphatases in the cell, the loss of rapid phase desensitization in RGS4-deficient SAN myocytes likely indicates the loss of a GAP-dependent desensitization mechanism. It has been shown that RGS4 forms stable protein-protein interactions with both M 2 R 14 and GIRK3 15 channels, and, thus, it is proposed to be a component of an integrated kinetic scaffolding complex that promotes efficient coordinated regulation of both G protein and GIRK activation.…”
Section: Discussionmentioning
confidence: 99%
“…For GIRK current desensitization, two phases can be resolved. The slower one takes several minutes and probably is mediated by G-protein receptor kinases (GRKs, also known as ␤ARKs) (5,6). As for the acute desensitization that occurs within a minute, dephosphorylation of K ACh channels in atrial myocytes has been implicated because it is augmented by cytoplasmic ATP (4).…”
mentioning
confidence: 99%